DIVERSIFIKASI PRODUK WISATA DALAM STRATEGI PENGEMBANGAN OBJEK WISATA KOTA MEDAN - Sitompul, Rajin (Jurnal Ilmiah Akomodasi Agung, 2024)
The trust of the world community about a product of a region is increasingly real. This is due to the expansion of information channels through the use of internet technology, the development of aviation technology and the easy accessibility of visits to one area. All of this makes tourism products more real, so that these tourism attractions are easier to achieve. In connection with this condition, tourists' perceptions are increasingly real in digesting their journey. In accordance with objects that are promoted through online and non-online media, and producers are able to buy and visit them many times wherever they are. That said, with the number of tourists increasing every day every week, every month and every year, at an object, conditions cause the state of the tourist attraction to be disrupted and can get worse. This is one of the important indicators in the management of an object and tourist attraction, where the comparison between visits to products and their repair (maintenance) must be carried out in a balanced way. So that the performance felt by tourists is the essence of processing the object. If the condition of the object is under the condition of the previous object, then the tourist's expectations are not satisfied. If the condition of the object meets expectations, tourists will be satisfied. If the condition of the object exceeds expectations, tourists are very satisfied or happy. The purpose of the research in this study is: to inform the public that the objects that have existed so far are not monotonous, only showing existing tourist objects. Objects that have been recorded and widely promoted and have been visited for many years. However, there are still other tourist objects that can become popular if they are shown and promoted to the public with different concepts from the previous method. So far, the goverrment has only shown objects that have been widely promoted. This object is an area that is always promoted domestically and abroad. Tourists only recognize objects that are promoted by the Tourist Information Center (TIC) service agency at the Medan City and Tourism Office. It is known that there are 5 factors of tourists' perception of tourism services, namely: 1). tangibility factor; 2). reliability factor; 3). responsiveness factor; 4). assurance factor; and 5). empathy factor. As well as to analyze the management strategy of the Medan city Culture and Tourism Office. This research was conducted at the Department of Culture and Tourism in the city of Medan. This study used the opinions of informants who were selected as samples. Data is collected through the results of interviews with tourists who use products/services. Then it was analyzed using qualitative descriptive data analysis and presented in narrative form. This research is expected to be able to find out tourists' perceptions of the services of the Medan City Culture and Tourism Office; to find out the management strategy so that in the future it can be managed better. Finally, it can contribute to making tourism management policies by the local government. Based on the results of the analysis of all factors/dimensions of tourist perceptions of the services of the Medan City Culture and Tourism Office, they are in the dissatisfied category. To make service quality into excellent service, managers need to improve the skills, knowledge, and attitudes of their staff in such ways as: paying attention to the appearance of officers, providing appropriate information, providing timely services, avoiding mistakes when providing services, being able to respect tourists when serving, maintaining attitude when serving, increasing the knowledge of staff, being able to use language that is easy and clear, and clean when serving, calling tourists names, paying attention to tourist requests. This study aims to determine the Implementation of Product Diversification Strategy which includes concentric diversification and horizontal diversification. This study uses a qualitative descriptive research method. The sampling technique used is purposive sampling, namely the sampling technique with certain considerations. This study used in-depth interviews, observation, documentation studies, and analyzed using triangulation and source triangulation techniques.